Dynamic Ultrasonic Wave Generators as an Alternative Technology to Field Rat Repellents - Muhammad Jauhar Vikri; Roihatur Rokhmah (Ultima Computing : Jurnal Sistem Komputer, 2022)
The case of crop failure caused by pest attacks is one of the problems in agriculture that is always interesting to study. Apart from weather factors, pest attacks on rice and corn agricultural commodities often occur just before harvest time. Currently, farmers often use toxic materials and even electricity as a means to repel and eradicate rat pests. However, this method can be dangerous for the farmers themselves. There have even been several cases of death due to electrical equipment installed in agricultural areas. Based on these problems, a pest repellent will be made by utilizing ultrasonic waves from a solar-powered power source so that it can be used efficiently, practically and safely. This tool is built using IC NE556C, Solar Panel, LDR Sensor (Light Dependent Resistor), and Ultrasonic Piezo PTC 4000 Speaker. IC NE556C timer and ultrasonic wave multivibrator are used to generate ultrasonic waves randomly according to the program. The purpose of making this tool is as an alternative to field mouse pest repellent using ultrasonic waves by utilizing solar energy in handling pests in agricultural areas.